2017
DOI: 10.1039/c7dt01993a
|View full text |Cite
|
Sign up to set email alerts
|

A versatile route to homo- and hetero-bimetallic 5f–5f and 3d–5f complexes supported by a redox active ligand framework

Abstract: The salt-elimination reaction of the complex [NaU(bis-salophen)] with metal halides provides an entry to the synthesis of well-defined homobimetallic uranium-uranium and rare heterobimetallic uranium-cobalt and uranium-nickel complexes supported by a redox-active dinucleating ligand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 41 publications
0
23
0
Order By: Relevance
“…This feature can result in uranium-metal communication, for example in a trinuclear [Co-O]U]O-Co] complex that exhibits a magnetic exchange and a slow relaxation at a reversal barrier temperature of 30.5 AE 0.9 K, resulting in 5f-3d single molecule magnetism. [12][13][14][15][16] We have also reported the exclusively group(I) mono-oxo metalated uranyl(V) complexes [(py) 3 17 We have shown that uranyl(VI) to uranyl(V) reduction is possible by both homolytic bond cleavage 18 and sterically induced reduction, 19 as well as via a direct reductive metalation. 20,21 Importantly, uranyl(VI) complexes in which one oxo group is coordinated by a Lewis acid group, such as a borane or metal complex, are activated towards singleelectron reduction by as much as 0.6 V. 9,10,[22][23][24][25] This has been used to direct the functionalisation of the oxo group by d-and pblock reagents.…”
Section: Introductionmentioning
confidence: 93%
“…This feature can result in uranium-metal communication, for example in a trinuclear [Co-O]U]O-Co] complex that exhibits a magnetic exchange and a slow relaxation at a reversal barrier temperature of 30.5 AE 0.9 K, resulting in 5f-3d single molecule magnetism. [12][13][14][15][16] We have also reported the exclusively group(I) mono-oxo metalated uranyl(V) complexes [(py) 3 17 We have shown that uranyl(VI) to uranyl(V) reduction is possible by both homolytic bond cleavage 18 and sterically induced reduction, 19 as well as via a direct reductive metalation. 20,21 Importantly, uranyl(VI) complexes in which one oxo group is coordinated by a Lewis acid group, such as a borane or metal complex, are activated towards singleelectron reduction by as much as 0.6 V. 9,10,[22][23][24][25] This has been used to direct the functionalisation of the oxo group by d-and pblock reagents.…”
Section: Introductionmentioning
confidence: 93%
“…Actinide complexes exhibiting magnetic exchange properties are rarely mentioned in the literature [1,2], relatively to the rich d-transition metal magnetochemistry. Most documented cases involve diuranium(V) systems [8,[23][24][25][26][27]37,[49][50][51]106,[111][112][113][114][115][116], and only a few studies of magnetic coupling in diuranium(III) and (IV) complexes or mixed uranium(IV)-transition metal have been reported [46,52,105,107,[117][118][119][120][121][122]. Among them, remarkable examples of unusual U(V)-U(V) coupling involving a pentavalent bis(imido) uranium dimer [106] and within diuranium(V) dioxo diamond cores [46,49,[114][115][116][123][124][125][126] have been reported, which can exhibit Néel temperatures of up to 70 and even 110 K [23,24,27,114,115,127].…”
Section: Magnetic Coupling Interactionsmentioning
confidence: 99%
“…To date, only scarce examples of mixed (5f-3d) actinide/transition metal complexes exhibiting magnetic exchange interactions are found in the literature [1,[43][44][45]114,115,[118][119][120][121]. Moderate ferromagnetic exchange coupling was measured by J. D. Rinehart et al (2007) [1,122] for the linear chloride-bridged 5f−3d heterometallic mixed trinuclear U IV /M II /U IV dimethylpyrazolate (cyclam)M II [(µ-Cl)U IV (Me 2 Pz) 4 ] 2 (M II = Ni, Cu, Co, Zn) cluster shown in Figure 29.…”
Section: Mixed Actinide/transition Metal (5f-3d) and Actinide/lanthanmentioning
confidence: 99%
“…One identified strategy for directinga nd stabilising early/late heterobimetallic assemblies is to take profit of bifunctional bridging ligands featuring two distinct coordination motifs: one hard, able to form strongb onds with oxophilic early TMs, and one soft, featuring as trong affinity for late TMs. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] In most examples reported to date in the literature, the latemetald onor is ap hosphine-derivedm oiety.Encouraged by the flagshipr ole played by N-heterocyclic carbene (NHC) organometallicc omplexes in homogeneous catalysis, especially with late TMs, [21][22][23][24][25][26] we have identified alkoxy-functionalised NHC ligands [27][28][29][30] as promising alternatives.Q uite surprisingly,t ot he best of our knowledge,t hese ligandsh ave not been specifically used to stabilisee arly/late heterobimetallic assemblies so far. In as ingle precedent, Arnold and co-workersr eported that UL 4 (L = OCMe 2 CH 2 [1-C(NCHCHNiPr)]) reacts with molybdenuma nd tungsten carbonyls to yield new entities formulated as [UL 4 Mo(CO) 4 ]a nd [UL 4 W(CO) 5 ], respectively.Y et it is unclear how the metals are arranged in these compounds.…”
Section: Introductionmentioning
confidence: 99%